Cronos acorrentado: cultura histórica, tempo e memória nos contos de João Guimarães Rosa - Silva, Amanda Teixeira da (2011)
The study has as objective to discuss the representations of history, time and memory produced in João Guimarães Rosas‟ literature. The research examined how these three elements appear in the stories of Primeiras Estórias e Tutaméia-Terceiras Estórias. We also analyzed his interviews, as well as letters exchanged with friends, relatives and family, and notes recorded in diaries, notebooks and studies for the work. This research aims to demonstrate that the historical culture of an individual is not formed only by the school or academic knowledge, but by a wide range of knowledge and interests that lie beyond the historiography and history itself. This dissertation considers that there is, in Guimarães Rosa´s work, a constant need of evasion of time. The author criticizes the history in that it favors the study on momentary and deeply desecrated events. Memory becomes, in his work as a literary resource whose purpose is to restore the sacred dimension to events. This study is linked to the research line "History Teaching and Historical Knowledge" of Paraíba Federal University Post Graduation Program, with a major in History and Historical Culture , and intends to analyze the readings and experiences that guided the statements made by Guimarães Rosa, throughout life, "against the story."